-6(w+6)=1

Simple and best practice solution for -6(w+6)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(w+6)=1 equation:


Simplifying
-6(w + 6) = 1

Reorder the terms:
-6(6 + w) = 1
(6 * -6 + w * -6) = 1
(-36 + -6w) = 1

Solving
-36 + -6w = 1

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + -6w = 1 + 36

Combine like terms: -36 + 36 = 0
0 + -6w = 1 + 36
-6w = 1 + 36

Combine like terms: 1 + 36 = 37
-6w = 37

Divide each side by '-6'.
w = -6.166666667

Simplifying
w = -6.166666667

See similar equations:

| y=-4/3(1.3333)-8 | | 2x+1-5=7-1 | | 11-2x=-17 | | 4x+2=53 | | 7=8(1+2r)-5(1+3r) | | -3(4-3n)=-66 | | x+y+xy=120 | | 4/x+1/9= | | 5=5m-6 | | 2/5h-7=12/5h-2h+4 | | 5=5m+6 | | -63=5+4(1-3x) | | -6xy-2xz-9x+1=4y+4 | | x(2)+5x+6= | | 15-3b=5b+2b+18-3 | | -72=-9(m+12) | | -14=6x+34 | | (t+20)=(t-10)+t | | 3g-2g= | | 1x+10=6 | | 6x=12+3y | | -5x=14-x-2 | | 8(2-t)=-4t | | (2x+5)(3x-7)= | | x+26(2)=264 | | 8+8x=80 | | 8+-29=-24+3t | | 4(k+5)=2k+10 | | 6r^2-19r-4=0 | | -1+58x=57x+1 | | 3G-2g=12 | | 5-3=15 |

Equations solver categories